Epithelioid trophoblastic tumor of the uterus: currently available diagnostic methods, determining an effective treatment strategy (case report) - S. N. Mamedli; M. A. Chekalova; L. A. Meshcheryakova; A. F. Maslennikov; N. A. Meshcheryakova; А. I. Karseladze; V. V. Kuznetsov (ABV-press, 2019)
Gestational trophoblastic disease is a group of pathological conditions of the trophoblast, which includes both benign and malignant forms. Epithelioid trophoblastic tumor is one of the rare malignant trophoblastic tumors. The tumor develops from intermediate trophoblastic cells and is characterized by the absence of villi and presence of clusters of atypical mononuclear trophoblastic cells and elements of syncytiotrophoblast, similar to epithelial cells in their appearance. Patients with epithelioid trophoblastic tumors usually have extragenital tumor foci with no pathology detected in the uterus. Pelvic ultrasound is an essential stage of such patients' examination. Conventional ultrasound and Doppler ultrasonography are informative, reliable, easy to use, and non-invasive diagnostic procedures that provide wide opportunities of dynamic evaluation of the disease during the course of anticancer therapy and subsequent follow up. Comprehensive diagnostics enables timely detection of a rare morphological variant of a malignant trophoblastic tumor and ensures right decision on the treatment strategy, which is the key to a favorable outcome with preserved reproductive function.